1962
DOI: 10.1111/j.1365-2672.1962.tb01121.x
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative and Qualitative Study of the Lipolytic Activity of Single Strains of Seven Bacterial Species

Abstract: Summary Single strains of Serratia marcescens, Staphylococcus aureus, Micrococcus freudenreichii, Pseudomonas hydrophila, Achromobacter fischeri, Bacillus subtilis and Bacillus cereus were examined for their lipolytic activity, qualitatively using different lipolysis detecting media and quantitatively by means of acid production. The substrates investigated were olive oil, tributyrin, ethyl laurate and ethyl butyrate. The effect of temperature and pH on lipolytic activity, as measured by acid production, has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1963
1963
1988
1988

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Lipase activity is characteristic of strains of S. marcescens (Hugo and Beveridge, 1962;Edwards and Ewing, 1972;Owens, 1974). The absence of mono-or di-glycerides as hydrolysis products indicated that the lipase released all the fatty acids of triolein with equal facility, independently of their position.…”
Section: Discussionmentioning
confidence: 99%
“…Lipase activity is characteristic of strains of S. marcescens (Hugo and Beveridge, 1962;Edwards and Ewing, 1972;Owens, 1974). The absence of mono-or di-glycerides as hydrolysis products indicated that the lipase released all the fatty acids of triolein with equal facility, independently of their position.…”
Section: Discussionmentioning
confidence: 99%
“…Growth stimulation or inhibition by bile was determined by adding 2% (wt/vol) Oxgall (Difco) to PYFG broth. Lipase activity was detected in PYFG agar plates with 1% (vol/ vol) glycerol tri-n-butyrate added as described by Hugo and Beveridge (17). A positive reaction was detected by a zone of clearing around the colony.…”
Section: Methodsmentioning
confidence: 99%
“…Since a positive reaction can be produced both by a lipase and a lecithinase, special media were also used to differentiate between these two enzyme activities. Tributyrin agar was prepared after sonic treatment of the substrate according to Hugo and Beveridge (1962). Lecithin agar contained 5 g of lecithin per 1 of agar medium (T. Wadstrom, P. Allestam and R. Mollby, to be published).…”
Section: Methodsmentioning
confidence: 99%